A new species of Eriotheca (Malvaceae: Bombacoideae) from Espírito Santo, eastern Brazil - de Carvalho-Sobrinho, Jefferson Guedes (Phytotaxa, 2013)
A new species of Eriotheca (Malvaceae: Bombacoideae) from a granitic rock outcrop in the state of Espírito Santo, eastern Brazil, is described and illustrated. Eriotheca saxicola represents the first reference of a xylopodium-like organ for the genus. The new species is compared to its putative closest relatives and notes on its distribution, ecology, and phenology are provided.